Gender differences in the consumption of alcohol mixed with caffeine and risk of injury. (9th October 2019) - Roemer, Audra; Stockwell, Tim; Zhao, Jinhui; Chow, Clifton; Vallance, Kate; Cherpitel, Cheryl
Abstract: Introduction and Aims: There is increasing evidence suggesting the consumption of caffeinated alcoholic beverages is associated with risks over and above alcohol use on its own; however, research in this area remains limited. We examined whether gender differences existed in the relationship between the combined use of alcohol and caffeine (Alc + Caff) and risk for injury. Design and Methods: This emergency department study utilised case–control and case‐crossover analyses to examine in situ session specific Alc + Caff use and injury risk for men and women, while controlling for socio‐demographic variables, dose of alcohol and caffeine, other substance use, risk‐taking propensity and context. The sample comprised 2804 individuals aged 18‐years or older who presented to three hospital emergency departments in British Columbia. Results: A relationship between Alc + Caff use and increased risk of injury was confirmed. Further, gender differences were found in the risk relationship between Alc + Caff use and injury. Women were found to have a higher risk injury propensity following Alc + Caff use in both the case–control (OR = 3.10, 95% CI = 1.78, 5.84) and case‐crossover analyses (OR = 3.21, 95% CI = 1.69, 6.12), relative to men (OR = 1.69, 95% CI = 1.30, 2.30; OR = 1.38, 95% CI = 1.08, 1.86). These results remained even after controlling for demographic factors, risk‐taking, context and other substance use. Discussion and Conclusions: Women may be at higher risk of injury than men following the consumption of alcohol mixed with caffeine. The findings offer support for differential low‐risk drinking guidelines for men and women and the restriction and regulation of the sale and availability of caffeinated alcoholic beverages.